2015
DOI: 10.1002/pmic.201400476
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics analysis of bodily fluids in pancreatic cancer

Abstract: Proteomics study of pancreatic cancer using bodily fluids emphasizes biomarker discovery and clinical application, presenting unique prospect and challenges. Depending on the physiological nature of the bodily fluid and its proximity to pancreatic cancer, the proteomes of bodily fluids, such as pancreatic juice, pancreatic cyst fluid, blood, bile and urine, can be substantially different in terms of protein constitution and the dynamic range of protein concentration. Thus, a comprehensive discovery and specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 132 publications
(143 reference statements)
1
57
0
Order By: Relevance
“…Proteomics is an emerging technology to quickly survey altered cellular functions through a large‐scale gene determination and, therefore has been employed in a variety of clinical studies . However, potential biomarker proteins in body fluids are often present at low levels, requiring sensitive techniques.…”
mentioning
confidence: 99%
“…Proteomics is an emerging technology to quickly survey altered cellular functions through a large‐scale gene determination and, therefore has been employed in a variety of clinical studies . However, potential biomarker proteins in body fluids are often present at low levels, requiring sensitive techniques.…”
mentioning
confidence: 99%
“…Proteomics approach has been widely adopted in studies of human diseases including cancer (Frantzi et al, 2015; S. Pan, Brentnall, & Chen, 2015; Petricoin et al, 2002; Tsai et al, 2015), multiple sclerosis (Farias, Pradella, Schmitt, Santos, & Martins-de-Souza, 2014) and schizophrenia (Al Awam et al, 2015; Nascimento & Martins-de-Souza, 2015).…”
Section: Overview Of Omics Technologies and Association Studiesmentioning
confidence: 99%
“…However, these studies have found many protein candidates, which can potentially improve prognosis, diagnosis, and effectiveness of treatment. More recent proteomic studies also used body fluid samples to identify protein markers for bladder cancer (Frantzi et al, 2015), pancreatic cancer (S. Pan et al, 2015) and hepatocellular carcinoma (Tsai et al, 2015).…”
Section: Overview Of Omics Technologies and Association Studiesmentioning
confidence: 99%
“…As TDSFs are diagnostically more important than the elements within the liver niche, it would not be necessary to access liver tissue in premetastatic phases. In fact, it was recently demonstrated for pancreatic cancer [66] that it should be feasible to detect TDSFs in body fluids during niche-creating inflammation or premalignant phases in a proteomic approach. Regarding the premetastatic niche in the liver, it will be important also to demonstrate the metastasis-promoting activation of specific liver cells by TDSFs in patients.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%